[RETRACTED] Shaping Southeast Asian Taste: Curry as Historical Evidences of Muslim Trade Networks in the Indian Ocean - Bambang Widyonarko (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2023)
This article has been retracted following an action of violating against publication ethics. The Journal of Islamic History and Manuscript has just learned that the article has been proven to have plagiarized another article entitled